Improving Student Listening Ability Through Audio-Visual Application At Smpn 2 Painan - Yefridelti Yefridelti (Fakultas Sastra Universitas Ekasakti, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to